Implementation of Googles Technology in Android Mobile App "Kediri City Fasum and Fasos Information System" - Nugroho, Benni Agung; Izzah, Abidatul (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2018)
There are so many public facilities (FasUm) and social facilities (FaSos) spreading all over the city. So that, many people do not know how to find and reach the location. Therefore, a mobile application becomes necessary to help solving problems in introducing and informing the location of those important facilities; thus, discovering and locating them can be simplified. This study aims to develop an android application providing information of public and social facilities. The application was built utilizing Googleâs features consisting of Google Sign In, Google Places API, Google Custom Search Engine, and Google Map. The application was developed in several steps; requirement analysis, system design, implementation, and testing. The application provides information, routes, related news, and location markers of public and social facilities from the app contributor and Google Services. The developed application has been compared with Google Map application. The result shows that it provides some features which are better than the existing app.Â